Disseminating the Islamic Concep in Conservation of Environment: Study Insights From Bangladesh - Shakil Ahmed; Moztafizur Rahman (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2025)
Human life and the environment are inextricably linked to each other. The environment provides all the necessary elements important to human existence. But the mankind has some duties too. But we are often avoiding these duties. Though we know the impact of environment in our lives but awareness has been a long due. Even integrating it with general education, campaigns, legal measures often fall short in establishing the thing. In this study we tried to analyze if we can solve the problem by connecting religion and environment. This study disseminates the conservation of the environment in accordance with the rules of Qur'an and Hadith, and conducts surveys among environmentalists and Islamic thinkers to find out how practical and useful these rules of the Islam are in protection of the environment. Information about the rules of Islam on conservation of the environment has been taken through conducting questionnaire survey and FGD (Focus Group Discussion) among Islamic thinkers. In this case, they have expressed the opinion that it is possible to protect the environment in accordance with Islamic law. Environmentalists were asked if it was possible to protect the environment based on Islamic rules. 70% expressed the opinion that protection of the environment is possible if Islamic rules are properly implemented. But rest of them have expressed different views and said that beside Islamic law, environmental law needs to be updated and implemented properly to protect the environment. Similar studies have been conducted in other countries also. Indonesia and Malaysia are prominent of them. Furthermore, it has been proved that the connecting environmental conservation with Islamic teachings provide impactful results. This study aims to correlate the Islamic concepts in preserving the environment and their impacts in perspective of Bangladesh.